AAV-Delivered Antibody Mediates Significant Protective Effects against SIVmac239 Challenge in the Absence of Neutralizing Activity - Fuchs, Sebastian; Martinez-Navio, Jose M.; Piatak, Michael; Lifson, Jeffrey D.; Gao, Guangping; Desrosiers, Ronald C. (PLoS Pathogens, 2015)
Long-term delivery of potent broadly-neutralizing antibodies is a promising approach for the prevention of HIV-1 infection. We used AAV vector intramuscularly to deliver anti-SIV monoclonal antibodies (mAbs) in IgG1 form to rhesus monkeys. Persisting levels of delivered mAb as high as 270 ?g/ml were achieved. However, host antibody responses to the delivered antibody were observed in 9 of the 12 monkeys and these appeared to limit the concentration of delivered antibody that could be achieved. This is reflected in the wide range of delivered mAb concentrations that were achieved: 1-270 ?g/ml. Following repeated, marginal dose, intravenous challenge with the difficult-to-neutralize SIVmac239, the six monkeys in the AAV-5L7 IgG1 mAb group showed clear protective effects despite the absence of detectable neutralizing activity against the challenge virus. The protective effects included: lowering of viral load at peak height; lowering of viral load at set point; delay in the time to peak viral load from the time of the infectious virus exposure. All of these effects were statistically significant. In addition, the monkey with the highest level of delivered 5L7 mAb completely resisted six successive SIVmac239 i.v. challenges, including a final challenge with a dose of 10 i.v. infectious units. Our results demonstrate the continued promise of this approach for the prevention of HIV-1 infection in people. However, the problem of anti-antibody responses will need to be understood and overcome for the promise of this approach to be effectively realized.
EVALuna2:8298

Host Anti-antibody Responses Following Adeno-associated Virus-mediated Delivery of Antibodies Against HIV and SIV in Rhesus Monkeys - Martinez-Navio, Jose M.; Fuchs, Sebastian; Pedreno-Lopez, Sonia; Rakasz, Eva G.; Gao, Guangping; Desrosiers, Ronald C. (Molecular Therapy, 2016)
Long-term delivery of antibodies against the human immunodeficiency virus (HIV) using adeno-associated virus (AAV) vectors is a promising approach for the prevention or treatment of HIV infection. However, host antibody responses to the delivered antibody are a serious concern that could significantly limit the applicability of this approach. Here, we describe the dynamics and characteristics of the anti-antibody responses in monkeys that received either rhesus anti-simian immunodeficiency virus (SIV) antibodies (4L6 or 5L7) in prevention trials or a combination of rhesusized human anti-HIV antibodies (1NC9/8ANC195/3BNC117 or 10-1074/10E8/3BNC117) in therapy trials, all employing AAV1 delivery of IgG1. Eight out of eight monkeys that received the anti-HIV antibodies made persisting antibody responses to all three antibodies in the mix. Six out of six uninfected monkeys that received the anti-SIV antibody 4L6 and three out of six of those receiving anti-SIV antibody 5L7 also generated anti-antibodies. Both heavy and light chains were targeted, predominantly or exclusively to variable regions, and reactivity to complementarity-determining region (CDR)-H3 peptide could be demonstrated. There was a highly significant correlation of the magnitude of anti-antibody responses with the degree of sequence divergence of the delivered antibody from germline. Our results suggest the need for effective strategies to counteract the problem of antibody responses to AAV-delivered antibodies.
EVALuna2:8300